Three-dimensional optimization of La0.6Sr0.4Co0.2Fe0.8O3 cathode microstructure with particle radius constraint. (1st December 2021) - He, An; Onishi, Junya; Gong, Jiaming; Shikazono, Naoki
Highlights: Porous LSCF cathode microstructure is optimized with radius constraint. Reaction current is enhanced and the particle size is successfully constrained. Computational accuracy is ensured and grid-independency is achieved. Optimized results are independent from the initial structures. Effects of bulk ionic conductivity and exchange current density are investigated. Abstract: A numerical model is developed to optimize the La0.6 Sr0.4 Co0.2 Fe0.8 O3 (LSCF) cathode porous microstructure of solid oxide fuel cell (SOFC), in which the local radius constraints are applied. During the optimization, the LSCF porous microstructure is deformed and the total reaction current is maximized. A level-set method is utilized to parametrize the 3D microstructure, and an adjoint method is applied for the sensitivity analysis. In addition, in order to improve the computational accuracy and to make the optimized microstructure manufacturable, a radius constraint is imposed to ensure that the local radii are above the target value, where the interface is updated only when the local radius value is larger than the target radius. Computational results show that the sphere-shaped LSCF solid particles are preferred in terms of performance improvement. In addition, the computational accuracy is improved with the imposed radius constraint, and the total electrochemical reaction current in the optimal microstructure is improved comparing with the experimentall fabricated microstructure obtained with 3D recontruction technique. Furthermore, the optimized microstructure and performance of the LSCF cathode are independent from the initial cathode structures. Finally, the relation between Thiele modulus and the optimal microstructure is investigated by varying the ionic conductivities and exchange current densities. Graphical abstract: Image, graphical abstract